Vikings: power and cultural identities in the show of History Channel - Donstrup, Mayte (2018)
The aim of this paper is to study from an anthropological perspective the formation of identities in the Canadian tv-series Vikings (2013- ), created by Michael Hirst for The History Channel. With this purpose, we use a textual methodology of the most relevant fragments. The discussion of the results is organized around one main core point that shape the construction of identities in this show: power.